Buddhists Armed with Apples. - Barglow, Raymond (Tikkun (Duke University Press))
Provides an analysis of the advertisement for Apple Computer Inc. that represents the relationship between Western technological rationality and an ancient spiritual tradition. Issue on whether a high regard for science is incompatible with a spiritual perspective; Old stereotypes about technology; Benefits that can be obtained from the technology.